1999
DOI: 10.1001/jama.281.21.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Androstenedione on Serum Testosterone and Adaptations to Resistance Training in Young Men

Abstract: Androstenedione supplementation does not increase serum testosterone concentrations or enhance skeletal muscle adaptations to resistance training in normotestosterogenic young men and may result in adverse health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
8
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(147 citation statements)
references
References 40 publications
10
126
8
2
Order By: Relevance
“…Even though only 12-14% of androstenedione is converted peripherally to T, 37,38 this amount accounts for about half the circulating T in women. As the peripheral contribution to blood T is far greater in young adult women than men, ingestion of modest amounts of DHEA, androstenediol or androstenedione is likely to raise circulating T. For example, even a single 100-mg oral dose of androstenedione to two women increased their plasma T concentration four-and sevenfold, respectively, 39 whereas the same acute dose to men (n=10) did not a¡ect either free or total serum T. 32 A recent study, in which a single dose of androstenedione (100 mg) was administered to ten young women, showed that the plasma T concentrations increased from *1nmol/ L to a maximum mean of 25¢1nmol/ L at 75 min and remained signi¢cantly di¡erent from control values between 30 min and 8 h post-administration. 40 The mean exposure (as determined by area under the curve) to testosterone was greater than an order of magnitude compared to the control period, and the plasma concentrations observed were similar to those encountered in abuse of T for anabolic purposes.…”
Section: Effects On Muscle Size and Strength In Manmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though only 12-14% of androstenedione is converted peripherally to T, 37,38 this amount accounts for about half the circulating T in women. As the peripheral contribution to blood T is far greater in young adult women than men, ingestion of modest amounts of DHEA, androstenediol or androstenedione is likely to raise circulating T. For example, even a single 100-mg oral dose of androstenedione to two women increased their plasma T concentration four-and sevenfold, respectively, 39 whereas the same acute dose to men (n=10) did not a¡ect either free or total serum T. 32 A recent study, in which a single dose of androstenedione (100 mg) was administered to ten young women, showed that the plasma T concentrations increased from *1nmol/ L to a maximum mean of 25¢1nmol/ L at 75 min and remained signi¢cantly di¡erent from control values between 30 min and 8 h post-administration. 40 The mean exposure (as determined by area under the curve) to testosterone was greater than an order of magnitude compared to the control period, and the plasma concentrations observed were similar to those encountered in abuse of T for anabolic purposes.…”
Section: Effects On Muscle Size and Strength In Manmentioning
confidence: 98%
“…Following very large doses of DHEA (1600 mg/ day for 28 days) to ¢ve young eugonadal men, free and total serum T did not increase. 31 With regard to androstenedione, chronic administration of 300 mg/ day to male volunteers aged 19-40 years resulted in considerable inter-individual variability to changes in serum T. King et al 32 showed no signi¢cant increase in serum T over an 8-week administration period (n=10), whereas Leder et al 33 reported a signi¢cant increase after 7 days of administration (n=14), but only a few of those subjects (n=4) had serum T concentrations that exceeded the reference range. For androstenediol, Uralets and Gillette 35,36 administered the ¢ 4 and the ¢ 5 forms to male volunteers and reported urinary concentrations of T in the former study.…”
Section: Effects On Muscle Size and Strength In Manmentioning
confidence: 99%
“…Chrysin and 7,8-dihydroxyflavone have been proposed as aro- matase inhibitors (20). However, in vivo studies do not show proof of aromatase inhibitor activity by chrysin in rats or humans (21,22). Presumably, 7,8-dihydroxyflavone might not inhibit aromatase, either.…”
Section: Kinases a Binding Assay Demonstrated That Increasing Concenmentioning
confidence: 99%
“…54 Most studies have found no change in testosterone levels but have confirmed increasing estrogen levels in male individuals. 4 Specific to athletes, King et al 55 in 1999 published a series of 20 healthy male individuals with 8 weeks of standardized resistance training, whereby androstenedione was given in a double-blinded manner versus placebo. At the conclusion of the testing period, those who received the drug showed no change in any athletic measure or testosterone levels but were found to have significantly increased estrone and estradiol levels.…”
Section: Effectsmentioning
confidence: 99%